TLR4 and CD14 receptors expressed in rat pineal gland trigger NFKB pathway - Cruz-Machado, Sanseray da Silveira; Carvalho-Sousa, Claudia Emanuele; Tamura, Eduardo Koji; Pinato, Luciana [UNESP]; Cecon, Erika; Magno Fernandes, Pedro Augusto Carlos; Werneck de Avellar, Maria Christina [UNESP]; Ferreira, Zulma Silva; Markus, Regina Pekelmann (Wiley-Blackwell, 2010)
Nuclear factor-kappa B (NFKB), a pivotal player in inflammatory responses, is constitutively expressed in the pineal gland. Corticosterone inhibits pineal NFKB leading to an enhancement of melatonin production, while tumor necrosis factor (TNF) leads to inhibition of Aa-nat transcription and the production of N-acetylserotonin in cultured glands. The reduction in nocturnal melatonin surge favors the mounting of the inflammatory response. Despite these data, there is no clear evidence of the ability of the pineal gland to recognize molecules that signal infection. This study investigated whether the rat pineal gland expresses receptors for lipopolysaccharide (LPS), the endotoxin from the membranes of Gram-negative bacteria, and to establish the mechanism of action of LPS. Here, we show that pineal glands possess both CD14 and toll-like receptor 4 (TLR4), membrane proteins that bind LPS and trigger the NFKB pathway. LPS induced the nuclear translocation of p50/p50 and p50/RELA dimers and the synthesis of TNF. The maximal expression of TNF in cultured glands coincides with an increase in the expression of TNF receptor 1 (TNFR1) in isolated pinealocytes. In addition, LPS inhibited the synthesis of N-acetylserotonin and melatonin. Therefore, the pineal gland transduces Gram-negative endotoxin stimulation by producing TNF and inhibiting melatonin synthesis. Here, we provide evidence to reinforce the idea of an immune-pineal axis, showing that the pineal gland is a constitutive player in the innate immune response.
Keywords: lipopolysaccharide; melatonin; nuclear factor-kappa B; pineal gland; toll-like receptor 4; tumor necrosis factor